Dorothy must die : stories - Paige, Danielle (Novelist) (Paige, Danielle (Novelist). Dorothy must die series., 2015)
Three prequel novellas to the Dorothy Must Die series that follow Dorothy Gale as she transforms from good girl to Wicked Witch.